Feature Papers in NeuroSci : From Consciousness to Clinical Neurology - Parnetti, Lucilla; Paoletti, Federico Paolini; Gallart-Palau, Xavier (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on relevant findings in the field of neuroscience, ranging from cognitive neuroscience, including studies on human consciousness, to clinical neurology, including studies on autism and epilepsy. Furthermore, the latest methods in the expanding field of neuroscience from cognitive to clinical subdisciplines will also be available to the readers.